Experimental study on peat fire suppression through water injection in laboratory scale - Hafizha Mulyasih; Lasta A. Akbar; Mohamad L. Ramadhan; Arkan F. Cesnanda; Randitia A. Putra; Ridho Irwansyah; Yulianto S. Nugroho (Alexandria Engineering Journal, 2022)
Peat fires can persistently last for an extended period after being ignited, despite rainfall and firefighting efforts. The difficulty of peat fire suppression is mainly due to the smoldering spreading through the subsurface layer. This paper reports laboratory experiments of peat fire suppression by means of water injection directly to the subsurface hotspot. Natural peat samples (from Papua and Jambi, Indonesia) were used in this study. The experimental results show that water injection is more efficient than the water spray technique based on both suppression duration and water usage in extinguishing hotspot areas. The suppression duration of water injection is about half of those of water spray. To fully suppress the fire, Papuan peat required 4.22 ± 0.26 L of water per 1 kg of peat (L/kg-peat), while Jambi peat required 3.81 ± 0.03 L/kg-peat. This study contributes to a better understanding of the suppression dynamic of the water injection technique and proposes its implementation for early peat fire mitigation in the field.